2008
DOI: 10.1007/s10350-008-9200-0
|View full text |Cite
|
Sign up to set email alerts
|

Sulphomucin Expression in Ileal Pouches: Emerging Differences Between Ulcerative Colitis and Familial Adenomatous Polyposis Pouches

Abstract: Sulphomucin expression is increased in the mucous gel layer of the ulcerative colitis pouch compared with that of the familial adenomatous polyposis pouch. Sulphomucin expression is associated with colonization by sulphate-reducing bacteria and increased chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…The released sulfate may then be utilized by D. desulfuricans indicating that SRB may be dependent on other intestinal bacteria to cleave and release sulfate, necessary as a metabolite 74 . Within the setting of UC an increased presence of SRB has been identified by several groups, 31 , 32 , 90 with an association between D. desulfuricans and active inflammation being demonstrated by Rowen et al 32 SRB have also been found to be exclusive to ileal pouches fashioned for UC, 91 , 92 with their presence corresponding to the expression of sulfated mucins 92 . Further studies focusing on the co-colonization rates of MDB and SRB during both active and quiescent disease are necessary in order to fully elucidate the role SRB may play in the pathogenesis of UC.…”
Section: Mucin Degrading Bacteria: Syntrophic and Antagonisticmentioning
confidence: 98%
“…The released sulfate may then be utilized by D. desulfuricans indicating that SRB may be dependent on other intestinal bacteria to cleave and release sulfate, necessary as a metabolite 74 . Within the setting of UC an increased presence of SRB has been identified by several groups, 31 , 32 , 90 with an association between D. desulfuricans and active inflammation being demonstrated by Rowen et al 32 SRB have also been found to be exclusive to ileal pouches fashioned for UC, 91 , 92 with their presence corresponding to the expression of sulfated mucins 92 . Further studies focusing on the co-colonization rates of MDB and SRB during both active and quiescent disease are necessary in order to fully elucidate the role SRB may play in the pathogenesis of UC.…”
Section: Mucin Degrading Bacteria: Syntrophic and Antagonisticmentioning
confidence: 98%
“…10 Increased sulphomucin production has also been described in the ulcerative colitis pouch, which is more characteristic of the colon, while FAP pouches retain a more sialomucin predominant mucus layer. 11 …”
Section: Introductionmentioning
confidence: 99%
“…79,82,86 These data suggest that the microenvironment of the ileal pouch in UC patients predisposes individuals to colonisation by specific bacterial populations, such as SRB, which can then increase the likelihood for developing pouchitis. 87 During a pouchitis episode, reduced bacterial diversity of the ileal pouch has been described, 81,82,86 that includes a reduction of the anaerobic to aerobic ratio, seen in both mucosal biopsies 81,88,89 and faecal samples. 13,82,90 In particular, an increase in the abundance of Enterobacteriaceae 81, 82 and reduced abundance of Bacteroides 82, 86 and F. prausnitzii 82 have been described.…”
Section: Dysbiosis Of Pouch Microbiotamentioning
confidence: 99%